A bi-level approach for the management of microgrids. Issue 28 (2018) - Ferro, G.; Minciardi, R.; Delfino, F.; Rossi, M.; Robba, M.
Abstract: A bi-level Energy Management System (EMS) is here proposed for the day ahead schedule and real-time optimal control of microgrids. The upper-level optimization problem (UDP) takes into account active and reactive power flows and a detailed formalization of the system model, with the aim of minimizing costs and emissions. For the lower level decision problem (LDP), the optimal results of the UDP are taken as reference values for the plant's schedule, which can be slightly modified in real time due to the actual values of renewables and energy demands. An analytical solution for the LDP has been found, which allows a fast and simple implementation of the microgrid's schedule.